Microbial fuel cells—A preferred technology to prevail energy crisis. (11th January 2021) - Din, Muhammad Imran; Nabi, Amna Ghulam; Hussain, Zaib; Khalid, Rida; Iqbal, Mahroosh; Arshad, Muhammad; Mujahid, Adnan; Hussain, Tajamal
Summary: With ever increasing waste production worldwide, the development of newly emerging technologies is rising and advancing proportionately. Entailed instalment of sophisticated energy‐producing plants is constantly expanding to meet the socio‐economic demands of communities and industries. Innumerable superior technologies have been introduced to minimise waste pollution while reducing emissions of greenhouse gases hence, combatting the impact of global warming. This review shows energy conversion technologies including gasification, pyrolysis, incineration, landfill, and bioelectrochemical technologies mainly microbial fuel cell (MFC), microbial electrolysis cells (MECs) and microbial electrosynthesis (MES). Traditionally, incineration and landfill are the main mean of waste conversion but not favourable because of their side effects, economic viability, secondary pollution and difficulty in mechanical compression. Recently, biological processes including anaerobic digestion have gained huge interest but possess some inherent drawbacks and cannot provide a comprehensive solution for future waste management. Among energy converting technologies, bio‐electrochemical MFC system is highly preferred as an elementary, clean, safe, economically viable and environmentally beneficial technology. MFC a renewable energy technology possesses multidimensional applications of producing electric power and treat wastewater. In addition, the MFCs can be modified into MEC to generate hydrogen energy from various organic matters. Prospective modification recommendations for scale‐up application of this technology are also presented. Abstract : Large scale waste production and energy crises are important global issues. Many waste managing and energy generating technologies have been introduced. Thermal and non‐thermal technologies are discussed. Use of Microbial fuel cells technology for energy crisis as a preferred technology.